Sexuality and Religiosity: an integrative literature review (Research, Society and Development, 2021)
The influence of religion on human sexual practices has been studied over the years. The objective was to know the national and international scientific production about the relationship between sexuality and religiosity from 2012 to 2017. This is an integrative literature review. Scielo, Pubmed and BVS databases were consulted and the 167 articles were found, 40 of them being selected following the recommendations of the Prisma strategy. The results pointed to 3 thematic categories, namely: religiosity as a risk or protection factor in sexuality during the health/illness process, religiosity and sexuality in the life cycle and in population groups, and religiosity and sexuality in the prevention of HIV/AIDS. It was concluded that religion could interfere in the health-disease process; studying it is necessary for the understanding of the individual in different spheres, so that proposals of interventions can be applied according to the needs of the subject.